Analisis krisis sampah dan polusi plastik sebagai ancaman ekosistem sungai dan laut di indonesia - Aryanto, Pandhu Syach (Maliki Interdisciplinary Journal, 2026)
The crisis of waste and plastic pollution has become a serious threat to river and marine ecosystems in Indonesia due to the increasing production, consumption, and mismanagement of plastic waste. Approximately 10% of plastic waste is discharged into rivers, with an estimated 165 thousand tons per year flowing into the sea, resulting in the accumulation of toxic and persistent plastic debris and microplastics. These microplastics, formed through the extremely slow degradation of plastics, enter the food chain and harm aquatic organisms through tissue damage, metabolic disruption, and reduced survival rates. Plastic pollution also threatens coastal ecosystem stability and human health, indicating that this issue has evolved into a long-term ecological crisis. This study examines the sources and causes of plastic pollution, its impacts on river and marine ecosystems, and mitigation strategies through policy reinforcement, technological innovation, and multi-sector collaboration. The analysis highlights the urgency of strengthening waste management systems, limiting single-use plastics, enhancing environmental awareness, and implementing circular economy principles to reduce ecological risks and ensure the sustainability of Indonesia’s aquatic ecosystems.